Microcomputer-Based Assistive Device for Visually Impaired Athletes in Track and Field Events - Al Afghani, Rafly Ikhsanudin; Ghalib, Najwan Muhammad; Kahfi, Dadan Hamdalah; Tawakal, Bilal Insan; Septiany, Reka; Stephani, Mesa Rahmi (TEGAR: Journal of Teaching Physical Education in Elementary School, 2023)
The purpose of this research was to develop an innovative device as a replacement for a guide runner for visually impaired runners. The method used was Research and Development (RD) method with the ADDIE model. The samples of this research were selected through purposive sampling. The sample consisted of visually impaired athletes participating in national sprinting events. The population of this research consisted of three individuals. Data collection techniques involved interviews with athletes and coaches and speed measurements before and after using the microcomputer-based device. The results of the implementation of this activity showed that, by using the microcomputer-based device, athletes could adapt more quickly compared to adapt with a guide runner. The running speed of athletes using the microcomputer-based device indicates faster times compared to running with a guide runner. As a result, the microcomputer-based device can assist visually impaired athletes in running independently without a guide runner.